PENGARUH PEMAPARAN LASERPUNKTUR PADA TINGKAT (KEBUNTINGAN) KETEBALAN PERUT DAN FERTILISASI IKAN TAWES (PUNTIUS JAVANICUS) - MUHAMMAD SUMSANTO; IKROMATUN NAFSIYAH; SITI LESTARI (GANEC SWARA, 2023)
Tawes fish (Puntius javanicus) is a freshwater fish that is easy to cultivate but tawes fish can spawn naturally only during the rainy season. Meanwhile, the market demand for tawes is increasing and the availability of seeds is not enough to meet market demand. To overcome this problem, it is necessary to apply technological advances in the form of a biostimulator for the development of Tawes fish farming business. The biostimulator used is a laser. Several studies state that the application of the use of soft lasers can be used to accelerate gonadal maturation. The purpose of this study was to determine the level of fertility and fertilization of tawes fish (Puntius javanicus), as well as to determine the level of abdominal thickness after laserpuncture exposure to prospective female parents. The method used in this study was an experimental method with a completely randomized design. This study consisted of 5 treatments with 1 control with each treatment being repeated 3 times, laserpuncture exposure treatment in 2/6 parts of the body once a week for 1 month. Treatment duration of exposure to laserpuncture for 2 seconds, 4 seconds, 6 seconds, 8 seconds and control. The results showed that exposure to different laserpuncture beams gave highly significant different results on the fertility of tawes fish. The best treatment was exposure to laserpuncture for 6 seconds with a fertilization value of 95.20%. The water quality during the study was within normal limits for tawes life which included a temperature of 27.80C, dissolved oxygen (DO) of 7.58 mg/l and a pH of 7.65.